Adaptive body patterning, three‐dimensional skin morphology and camouflage measures of the slender filefish Monacanthus tuckeri on a Caribbean coral reef. (9th June 2015) - Allen, Justine J.; Akkaynak, Derya; Sugden, Arthur U.; Hanlon, Roger T.
<x xml:space="preserve">Abstract</x> The slender filefish is a master of adaptive camouflage and can change its appearance within 1–3 s. Videos and photographs of this animal's cryptic body patterning and behavior were collected in situ under natural light on a Caribbean coral reef. We present an ethogram of body patterning components that includes large‐ and small‐scale spots, stripes and bars that confer a variety of cryptic patterns amidst a range of complex backgrounds. Field images were analyzed to investigate two aspects of camouflage effectiveness: (1) the degree of colour resemblance between animals and their nearby visual stimuli; and (2) the visibility of each fish's actual body outline vs. its illusory outline. Most animals more closely matched the colour of nearby visual stimuli than that of the surrounding background. Three‐dimensional dermal flaps complement the melanophore skin patterns by enhancing the complexity of the fish's physical skin texture to disguise its actual body shape, and the morphology of these structures was studied. The results suggest that the body patterns, skin texture, postures and swimming orientations putatively hinder both the detection and recognition of the fish by potential visual predators. Overall, the rapid speed of change of multiple patterns, colour blending with nearby backgrounds, and the physically complicated edge produced by dermal flaps effectively camouflage this animal among soft corals and macroalgae in the Caribbean Sea.